Common Goods for Health: Economic Rationale and Tools for Prioritization. Issue 4 (2nd October 2019) - Gaudin, Sylvestre; Smith, Peter C.; Soucat, Agnès; Yazbeck, Abdo S.
Abstract: This paper presents the economic rationale for treating Common Goods for Health (CGH) as priorities for public intervention. We use the concept of market failure as a central argument for identifying CGH and apply cost-effectiveness analysis (CEA) as a normative tool to prioritize CGH interventions in public finance decisions. We show that CGH are consistent with traditional lists of public health core functions but cannot be identified separately from non-CGH activities in such lists. We propose a public finance decision tree, adapted from existing health economics tools, to identify CGH activities within the set of cost-effective interventions for the health sector. We test the framework by applying it to the 2018 Disease Control Priority (DCP) list of interventions recommended for public funding and find that less than 10% of cost-effective interventions unconditionally qualify as CGH, while another two-thirds may or may not qualify depending on context and form. We conclude that while CEA can be used as a tool to prioritize CGH, the scarcity of such analyses for CGH interventions may be partly responsible for the lack of priority given to them. We encourage further research to address methodological and resource challenges to assessing the cost-effectiveness of CGH intervention packages, in particular those involving large investments and long-term benefits.